Regulating the Electrical and Mechanical Properties of TaS2 Films via van der Waals and Electrostatic Interaction for High Performance Electromagnetic Interference Shielding - Deng, Fukang; Wei, Jianhong; Xu, Yadong; Lin, Zhiqiang; Lu, Xi; Wan, Yan‑Jun; Sun, Rong; Wong, Ching‑Ping; Hu, Yougen (Nano-Micro Letters, 2023)
Low-dimensional transition metal dichalcogenides (TMDs) have unique electronic structure, vibration modes, and physicochemical properties, making them suitable for fundamental studies and cutting-edge applications such as silicon electronics, optoelectronics, and bioelectronics. However, the brittleness, low toughness, and poor mechanical and electrical stabilities of TMD-based films limit their application. Herein, a TaS2 freestanding film with ultralow void ratio of 6.01% is restacked under the effect of bond-free van der Waals (vdW) interactions within the staggered 2H-TaS2 nanosheets. The restacked films demonstrated an exceptionally high electrical conductivity of 2,666 S cm−1, electromagnetic interference shielding effectiveness (EMI SE) of 41.8 dB, and absolute EMI SE (SSE/t) of 27,859 dB cm2 g−1, which is the highest value reported for TMD-based materials. The bond-free vdW interactions between the adjacent 2H-TaS2 nanosheets provide a natural interfacial strain relaxation, achieving excellent flexibility without rupture after 1,000 bends. In addition, the TaS2 nanosheets are further combined with the polymer fibers of bacterial cellulose and aramid nanofibers via electrostatic interactions to significantly enhance the tensile strength and flexibility of the films while maintaining their high electrical conductivity and EMI SE.This work provides promising alternatives for conventional materials used in EMI shielding and nanodevices. Highlights: 1 A flexible freestanding TaS2 film (thickness = 3.1 μm) exhibits an ultralow void ratio of 6.01%, an ultra-high electrical conductivity of 2,666 S cm−1, an electromagnetic interference shielding effectiveness (EMI SE) of 41.8 dB, an absolute EMI SE (SSE/t) of 27,859 dB cm2 g−1, and excellent flexibility withstand 1,000 bends without rupture. 2 The TaS2 composite films exhibit excellent EMI shielding properties and higher tensile strength with better mechanical flexibility, making them suitable for EMI shielding practical applications.